Pro-nociceptive and anti-nociceptive effects of a conditioned pain modulation protocol in participants with chronic low back pain and healthy control subjects - Rabey, M.; Poon, C.; Wray, J.; Thamajaree, C.; East, R.; Slater, Helen (Churchill Livingstone, 2014)
Background: People with chronic pain may exhibit pro-nociceptive phenotypes characterised partly by reduced conditioned pain modulation (CPM). Characterising variability in CPM in people with chronic low back pain (CLBP) may inform management. Objectives: To investigate pro/anti-nociceptive effects of a CPM protocol in age/sex-matched healthy controls (HCs) and people with CLBP. Design: Case-controlled trial (64 participants/group). Method: The CPM protocol involved: test stimulus (TS) (noxious pressure applied by algometer to lumbar region); conditioning stimulus (CS) (noxious heat applied by thermode to dorsal hand). CPM recruitment was measured by the change in pain intensity (rated on a numeric rating scale (NRS)) of the TS in the presence and absence of the CS. Results: Responses to this CPM protocol were variable for both groups with measures consistent with either inhibitory or facilitatory effects. A significantly greater proportion of facilitatory responses were seen in the CLBP cohort compared to HCs (73% versus 31%). In response to the CS, participants with CLBP demonstrated a mean increase in NRS scores (mean 1.3 points; p<0.001), while HCs did not (mean-0.2 points; p=0.35) and the between-group difference in change scores was significant (mean 1.4 points; p<0.001; effect size (Hedges' g): 1.03). Conclusion: In HCs and participants with CLBP this CPM protocol elicited responses consistent with varying pro/anti-nociceptive effects. The higher proportion of participants with CLBP demonstrating a facilitatory response suggests a pro-nociceptive phenotype may characterise this cohort.